Dynamic mechanism of constructing future time perspective in a daily life and life-span development - Shirai, Toshiaki (2025)
Future Time Perspective (FTP) is defined as a cognitive-motivational construct of an individual’s perception of their personal future. How do people consciously construct their FTP? This study presents case studies using both daily data (over 19 days) and longitudinal data (spanning 33 years), focusing on how goal-directedness (a measure of FTP) and hope interact to shape their trajectories. The results show that hope is high when individuals experience a connection between the present and future, accompanied by the integration of affect, cognition, and behavior. In contrast, perceived uncertainty reduces hope. Importantly, goal-directedness increases when individuals consciously set goals, make plans, and take actions for the future. This study sheds light on the conscious construction of FTP by being among the first to examine within-individual variability by combining both daily and longitudinal data in time perspective research.